Development of a Method for the Identification of Friction Coefficients in Sheet Metal Materials for the Numerical Simulation of Clinching Processes - Rossel, Moritz Sebastian; Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
In order to reduce the fuel consumption and consequently the greenhouse emissions, the automotive industry is implementing lightweight constructions in the body in white production. As a result, the use of aluminum alloys is continuously increasing. Due to poor weldability of aluminum in combination with other materials, mechanical joining technologies like clinching are increasingly used. In order to predict relevant characteristics of clinched joints and to ensure the reliability of the process, it is simulated numerically during product development processes. In this regard the predictive accuracy of the simulated process highly depends on the implemented friction model. In particular, the frictional behavior between the sheet metals affects the geometrical formation of the clinched joint significantly. This paper presents a testing method, which enables to determine the frictional coefficients between sheet metal materials for the simulation of clinching processes. For this purpose, the correlation of interface pressure and the relative velocity between aluminum sheets in clinching processes is investigated using numerical simulation. Furthermore, the developed testing method focuses on the specimen geometry as well as the reproduction of the occurring friction conditions between two sheet metal materials in clinching processes. Based on a methodical approach the test setup is explained and the functionality of the method is proven by experimental tests using sheet metal material EN AW6014.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Numerical and Experimental Fracture Mechanical Investigations of Clinchable Sheet Metals Made of HCT590X - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Key Engineering Materials)
In many areas of product manufacturing constructions consist of individual components and metal sheets that are joined together to form complex structures. A simple and industrial common method for joining dissimilar and coated materials is clinching. During the joining process and due to the service load cracks can occur in the area of the joint, propagate due to cyclic loading and consequently lead to structural failure. For the prevention of these damage cases, first of all knowledge about the fracture mechanical material parameters regarding the original material state of the sheet metals used within the clinching process are essential.Within the scope of this paper experimental and numerical preliminary investigations regarding the fracture mechanical behavior of sheet metals used within the clinching process are presented. Due to the low thickness of 1.5 mm of the material sheets, the development of a new specimen is necessary to determine the crack growth rate curve including the fracture mechanical parameters like the threshold against crack growth ΔK I,th and the fracture toughness K IC of the base material HCT590X. For the experimental determination of the crack growth rate curve the numerical calculation of the geometry factor function as well as the calibration function of this special specimen are essential. After the experimental validation of the numerically determined calibration function, crack growth rate curves are determined for the stress ratios R = 0.1 and R = 0.3 to examine the mean stress sensitivity. In addition, the different rolling directions of 0° and 90° in relation to the initial crack are taken into account in order to investigate the influence of the anisotropy due to rolling.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

New Approach for Versatile Self Piercing Riveting: Joining System and Auxiliary Part - Kappe, Fabian; Bobbert, Mathias; Meschut, Gerson (Key Engineering Materials)
The increasing use of multi-material constructions lead to a continuous increase in the use of mechanical joining techniques due to the wide range of joining possibilities as well as the high load-bearing capacities of the joints. Nevertheless, the currently rigid tool systems are not able to react to changing boundary conditions, like changing the material-geometry-combination. Therefore research work is crucial with regard to versatile joining systems. In this paper, a new approach for a versatile self-piercing riveting process considering the joining system as well as the auxiliary joining part is presented.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Load Path Transmission in Joining Elements - Steinfelder, Christian; Martin, Sven; Brosius, Alexander; Tröster, Thomas (Key Engineering Materials)
The mechanical properties of joined structures are determined considerably by the chosen joining technology. With the aim of providing a method that enables a faster and more profound decision-making in the spatial distribution of joining points during product development, a new method for the load path analysis of joining points is presented. For an exemplary car body, the load type in the joining elements, i.e. pure tensile, shear and combined tensile-shear loads, is determined using finite element analysis (FEA). Based on the evaluated loads, the resulting load paths in selected joining points are analyzed using a 2D FE-model of a clinching point. State of the art methods for load path analysis are dependent on the selected coordinate system or the existing stress state. Thus, a general statement about the load transmission path is not possible at this time. Here, a novel method for the analysis of load paths is used, which is independent of the alignment of the analyzed geometry. The basic assumption of the new load path analysis method was confirmed by using a simple specimen with a square hole in different orientations. The results presented here show a possibility to display the load transmission path invariantly. In further steps, the method will be extended for 3D analysis and the investigation of more complex assemblies. The primary goal of this methodical approach is an even load distribution over the joining elements and the component. This will provide a basis for future design approaches aimed at reducing the number of joining elements in joined structures.

A Method for Characterization of Geometric Deviations in Clinch Points with Computed Tomography and Transient Dynamic Analysis - Köhler, Daniel; Sadeghian, Behdad; Kupfer, Robert; Troschitz, Juliane; Gude, Maik; Brosius, Alexander (Key Engineering Materials)
When joining lightweight parts of various materials, clinching is a cost efficient solution. In a production line, the quality of a clinch point is primarily controlled by measurement of dimensions, which are accessible from outside. However, methods such as visual testing and measuring the bottom thickness as well as the outer diameter are not able to deliver any information about the most significant geometrical characteristic of the clinch point, neck thickness and undercut. Furthermore, ex-situ destructive methods such as microsectioning cannot detect elastic deformations and cracks that close after unloading. In order to exceed the current limits, a new non-destructive in-situ testing method for the clinching process is necessary. This work proposes a concept to characterize clinch points in-situ by combining two complementary non-destructive methods, namely, computed tomography (CT) and ultrasonic testing. Firstly, clinch points with different geometrical characteristics are analysed experimentally using ex-situ CT to get a highly spatially resolved 3D-image of the object. In this context, highly X-ray attenuating materials enhancing the visibility of the sheet-sheet interface are investigated. Secondly, the test specimens are modelled using finite element method (FEM) and a transient dynamic analysis (TDA) is conducted to study the effect of the geometrical differences on the deformation energy and to qualify the TDA as a fast in-situ non-destructive method for characterizing clinch points at high temporal resolution.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Numerical Investigation of the Tool Load in Joining by Forming of Dissimilar Materials Using Shear-Clinching Technology - Wiesenmayer, Sebastian; Müller, Martin; Dornberger, Peter; Han, Daxin; Hörhold, Réjane; Meschut, Gerson; Merklein, Marion (Key Engineering Materials)
Modern developments in the automotive sector are motivated by the objective of lowering the emission of pollutants. In contrast, growing demands for safety and comfort lead to a potential increase of the weight of vehicles. Thus, the consequent use of lightweight design is indispensable. This includes the use of different materials for the construction of car bodies. Because of various material properties, joining of dissimilar materials is challenging and requires often the application of non-thermic processes like riveting or clinching. These processes are limited by the mechanical properties of the joining partners. Especially the increasing use of ultra-high strength alloys, like the hot stamped steel 22MnB5, makes the development of new joining technologies necessary. One of these innovative technologies is shear-clinching. By combining shear-cutting and clinching in one process, this technology produces durable and tight connections of dissimilar materials with high differences regarding strength and formability. In contrast to shear-cutting the die-sided material has no contact with the punch. Since the process of shear-clinching is a combination of cutting and joining using the same tool, the tool loads differ from common shear-cutting. Especially cutting hot stamped steels is a challenge due to their high ultimate strength which leads to high tool loads. Thus, the analysis of the load condition is essential for the dimensioning of durable and wear resistant tools. Hence, the scope of this paper is a numerical investigation of the tool loads during the indirect cutting process and the subsequent step of joining by forming during shear-clinching. Since an experimental investigation of the occurring tool loads in the closed process is not practicable, the finite element method has to be used. Therefore, a damage-based numerical model is set up to enable the coupled simulation of the combined cutting and joining process and the resulting tool loads. This allows the analysis of the loads during the whole process, identifying the influences of materials and sheet thicknesses.

Shear-Clinching of Multi-Element Specimens of Aluminium Alloy and Ultra-High-Strength Steel - Han, Daxin; Hörhold, Réjane; Müller, Martin; Wiesenmayer, Sebastian; Merklein, Marion; Meschut, Gerson (Key Engineering Materials)
The newly developed joining-by-forming technology “shear-clinching”, features a potentially single-stage process for joining UHSS without requiring any additional elements. Foundational studies have focused on the functionality of shear-clinching at a one-element sample. To ensure the safety of the industrial application of the shear-clinching technology, an investigation with component-like samples with several joints is required. This paper presents a detailed analysis of the material behaviour during the shear-clinching process with multi-element specimens to evaluate the influence of the neighbouring joints. In order to describe the influence of the neighbouring joints, the deformations resulting from the bending and material displacement are recorded without contact after the joining process: locally around the joining point and globally over the entire sample size. To minimize such bending effects, a tool-sided adaptation is provided. The results show the high potential of shear-clinching joining by UHSS and give further recommendations for future multi-material application.

Separation of Hybrid Structures for the Reclaim of their Single Components - Schweizer, Swetlana; Becker-Staines, Anna; Tröster, Thomas (Key Engineering Materials)
The main objective for an economic and ecological use of raw materials is the achievement of closed raw material cycles. Because of that, not only the manufacturing procedures are important during the development of new materials but also the recycling processes. Within the increased use of lightweight construction in recent years, the application of multi-material or hybrid structures reach high significance for the automotive industry. In this development, especially the carbon fibre reinforced plastics (CFRP) gained its importance. However, currently there are no recycling strategies available for hybrid structures; complete recycling processes for CFRP are still expandable. This work presents methods for separation of hybrid structures made of metal and CFRP, as well as the corresponding process windows and the boundary conditions. The separation is performed by introduction of thermal heat and the behaviour of these bonded compounds is analyzed based on shear tensile tests. The results of these studies are used to develop a complete recycling process for reclamation of hybrid structures.

Development of a Testing Method for the Identification of Friction Coefficients for Numerical Modeling of the Shear-Clinching Process - Müller, Martin; Vierzigmann, Ulrich; Hörhold, Réjane; Meschut, Gerson; Merklein, Marion (Key Engineering Materials)
Global competition as well as social and scientific megatrends strongly influence the modern car manufacturing industry. One of the most important approaches is the implementation of lightweight constructions. Therefore, the usage of high performance materials with tailored properties gains importance. For safety-relevant components such as automotive passenger cells it is necessary to minimize deformation to reduce the risk of injury for the vehicle occupants during a car accident. Thus, hot stamped high-strength steels have been established. High-strength and low formability of this kind of materials represent new challenges for joining technologies. One possibility to join high-strength steels is the newly developed shear-clinching technology. Due to the use of a combined cutting and joining process, the connection of dissimilar materials with high difference in strength and formability can be achieved. Further research to ensure process reliability and to improve the strength of the joint is required. One possible approach for this is the numerical investigation of the material flow during the joining process. Therefore, the definition of process parameters for the finite element model is necessary. A big impact on the quality of the results has the accuracy of the used friction values. As established testing methods are not suitable for modeling the rather complex tribological system between the joining partners of the shear-clinching process, an innovative testing method is needed. Studies in the field of sheet-bulk metal forming already demonstrated the applicability of the ring compression test for sheet metals. This paper presents a concept for the adaption of the ring compression test to the specific needs of the investigated shear-clinching process. The numerical identification of the friction coefficients is validated by experimental data and first results are qualified by experimental and simulative shear-clinching joints.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Internal Flow-Turning - An Innovative Technology for the Manufacture of Tailored Tubes - Homberg, Werner; Rostek, Tim; Wiens, Eugen (Key Engineering Materials)
In order to optimise the material utilisation and improve the lightweight design of automotive parts tailored hollow profiles are needed, especially as semi-finished parts for hydroforming. Internal Flow-Turning is an innovative incremental forming technology which enables the manufacture of tubes featuring a varying wall thickness and a constant outer diameter. These characteristics facilitate the material feed at hydroforming processes significantly. In addition, the spinning-related forming technology improves the mechanical material properties, shape and dimensional accuracy, and the surface quality of parts produced.